1993
DOI: 10.1159/000462402
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of D Sites on Selected 'Weak D' and 'Partial D' Red Cells

Abstract: Measurements have been made of the number of available sites on 10 examples of red cells in which the only abnormality appeared to be a quantitative reduction in the expression of D (weak D cells); these estimates were carried out using three monoclonal anti-D antibodies, Fog-1, Brad-3 and Los-2. The values varied with the monoclonal antibody that was used and fell within the range of 170-1,870 sites/cell. A further 3 examples of weak D cells which had brought about immunisation following transfusion were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Not all reported D variants have been ex amined and a number of different techniques have been em ployed. The quantitative techniques employed include ag gregation [10][11][12], antibody coated rosette formation [13], radioisotopic labelling [14][15][16][17], ELISA [18] and flow cy tometry [19][20][21][22]. The number of D sites per cell (SPC) has been found to vary with different MAb-D for normal and weak D [17] and normal and D variant red cells [23], Cells belonging to the same D category also had different numbers of D SPC when quantified using the same anti-D [17,24].…”
mentioning
confidence: 99%
“…Not all reported D variants have been ex amined and a number of different techniques have been em ployed. The quantitative techniques employed include ag gregation [10][11][12], antibody coated rosette formation [13], radioisotopic labelling [14][15][16][17], ELISA [18] and flow cy tometry [19][20][21][22]. The number of D sites per cell (SPC) has been found to vary with different MAb-D for normal and weak D [17] and normal and D variant red cells [23], Cells belonging to the same D category also had different numbers of D SPC when quantified using the same anti-D [17,24].…”
mentioning
confidence: 99%
“…In the Netherlands one incident was identified where a unit of weak D donor blood (1470 Rh D SPC), mistakenly typed as D negative, caused primary immunization in a female transfusion recipient with no previous history of pregnancy or transfusion (Gorick et al, 1993). For D VI blood there has been no reported incidences of immunization after transfusion in D-negative recipients.…”
Section: Discussionmentioning
confidence: 99%
“…If the fetus has a weak D or partial D VI phenotype much fewer sites may be present due to decreased Rh D antigen expression (Gorick et al, 1993;Jones et al, 1996). It has been estimated that the SPC in weak D vary between 100 and 1870 sites per cell, and in D VI between 300 and 2900, although a recently characterized D VI category (type III; Wagner et al, 1998) has been shown to be able to have near-normal Rh D antigen expression.…”
mentioning
confidence: 99%
“…Both direct or indirect immunofluorescence may be used. Flow cytometry has been applied to determine absolute antigen densities for ABO [7] and Rh [8][9][10]. The antigen density of weak D cells may be quantitized [8,10,11].…”
Section: Overview Of Flow Cytometry Applications In Immunohematologymentioning
confidence: 99%
“…Flow cytometry has been applied to determine absolute antigen densities for ABO [7] and Rh [8][9][10]. The antigen density of weak D cells may be quantitized [8,10,11]. For other antigens, dosing effects and phenotype-related differences in antigen densities could be demonstrated [5,12].…”
Section: Overview Of Flow Cytometry Applications In Immunohematologymentioning
confidence: 99%